Key genes involved in the acquisition of oocyte competence - Crocomo, Letícia Ferrari; Landim-Alvarenga, Fernanda Da Cruz [UNESP]; Bicudo, Sony Dimas [UNESP] (Medicina Veterinaria (UFRPE), 2019)
Despite meiotic arrest at diplotene stage of prophase I, oocytes from most domestic mammals retain the capacity for gene transcription due to the presence of descondensation areas in chromatin. With meiosis resumption under stimulation from luteinizing hormone, however, this transcriptional activity is interrupted and resumed only with the activation of the embryonic genome. So, all the process of oocyte maturation, fertilization and early embryogenesis, as well as the expansion of cumulus cells depend on the proper transcription and storage of messenger RNAs still during the meiotic arrest which, at appropriate moments and under specific signals, will be recruited for translation and protein synthesis. In this context of genetic control, some transcripts stand out due to their importance in the events that govern the acquisition of oocyte competence and the initial embryogenesis, such as MATER, ZAR1, GDF9, BMP15, BAX, and BCL2, expressed in oocytes, beyond the PTGS2, PTX3, HSA2, TNFAIP6, and GREMLIN, expressed on cumulus cells. Thus, due to theme relevance, this review aims to explore the oocyte-cumulus interaction and to compile the knowledge regarding the function and profile expression of the main maternal transcripts considered essential for the proper oocyte and embryonic development.
Principais genes implicados na aquisição de competência oocitária
Keywords: Apoptosis; Embryo; Granulosa cells; mRNA; Oocytes